Installation Of Religious Moderation Values In A Pluralistic Society (Case Study In Giri Madia Lingsar Village, Lobar) - Hakim, Lukman; Sugiarto, Fitrah; Ahlan, Ahlan; Fuadi, Mi'raj (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study analyzes the strategy and effectiveness of instilling religious moderation values in a pluralistic society. The values of religious Moderation promote tolerance, respect for diversity, and interfaith cooperation in overcoming differences of faith. The research method used is qualitative research with a case study approach with data collection techniques in the form of observation, interviews, and document analysis to obtain a comprehensive picture of the implementation of religious moderation values in daily life in the people of Giri Madia Lingsar Village, West Lombok. The results showed that cultivating religious moderation values can act as a catalyst to build harmony and unity in a pluralistic society. Some moderation values that need to be applied include National Commitment, Tolerance, Building Harmony, and Accommodating Local Culture, which are very important to be instilled in the community, especially in the community in Giri Madia Village, which is a plural community group with two religious groups namely Islam and Hinduism and has lived together for many years.